Ananas comosus (L.) Merr.: a mini review of its therapeutic properties / Izzati Awang Rahman ... [et al.] - Awang Rahman, Izzati; Mohamed, Emida; Camalxaman, Siti Nazrina; Haron, Norhisham; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Ananas comosus (L.) Merr. is a monocot perennial plant that belongs to the Bromeliaceae family. It is known as pineapple and is a common fruit in Malaysia. This review discusses its wide variety of phytochemical compounds and pharmacological properties. Based on the review, several parts of the A. comosus plant have been studied which include its stem, peel, crown, leaves and fruits. Alkaloids, α-amylase, acid and alkaline phosphatase, anthraquinones, bromelain, cardiac glycoside, coumarins, flavonoids, glycoside, inulin, napthoquinones, phenols, phytate, phytosterols, polyphenols, quinine, ribulose biphosphate carboxylase, saponin, steroids, sterols, tacorin, tannins, terpenoids and triterpenes have been identified from several parts of A. comosus. Due to the enormous number of bioactive compounds, various therapeutic properties and activities were recorded. Extracts of the plant has been proven to have medicinal effects such as protein anti-aggregation, wound healing, anti-proliferative, pro-apoptotic, anti-rheumatic, anti-inflammatory, antioxidant, antimicrobial, anti-diabetic, anti-coagulant, anthelminthic, anti-hyperglycemic, anti-plasmodial, anti-pyretic and cardioprotective properties.